(untitled) (Baghdad Science Journal, 2020)
Microalgae present much usefulness for antimicrobial research because of its enormous biodiversity and rapid growth rate. From this study results it is reaveled that Chlamydomonas reinhardtii were isolated from a pond of water in the province of Diwaniyah. The culture supernatants were obtained when extracted with methanol solvent. Antimicrobial activity of extracts was tested for pathogens, and the best inhibition zone obtained was against Candida albicans (32mm), S.aureus (15mm), and to E.coli (9mm). While it showed no effect against both S.epidermidis and Klebsiella spp. Biofilm was formed by all tested isolates with differences in its strength formation. The C. reinhardtii Algal extract showed higher reduction of the existing Staphylococcus aureus biofilm and (10.9 %) was the remaining biofilm, while 55.21% and 54.98% were to Serratia spp. and Escherichia coli respectively, and it’s the lowest reduction. Klebsiella spp., Candida albicans, Acinetobacter spp., Staphylococcus epidermides, and Aspergillus sp. showed remaining biofilm as (16.7, 18.3, 19.6, 43.6, and 44.1) % respectively. The composition of the volatile compounds of the C. reinhardtii extract was determined by GC/MS. Different groups of compounds were identified such as hydrocarbons, phenols, alcohols and esters, and two bioactive compounds;1-Heptacosanol and Octadecyl chloride which is used in medical and pharmaceutical fields.These results provide an indication of the existence of hopeful antibiofilm compounds in the algal species under study. Further chemical studies are required to illuminate these compounds, structures and activity.